2015
DOI: 10.1093/ckj/sfv079
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to effective communication between veterans with chronic kidney disease and their healthcare providers: Table 1.

Abstract: BackgroundMany patients with chronic kidney disease (CKD) have insufficient knowledge about CKD, which is associated with poorer health outcomes. Effective patient–provider communication can improve CKD patients' knowledge, thereby augmenting their participation in self-care practices. However, barriers to addressing CKD patients' information needs have not been previously characterized.MethodsAdults with an estimated glomerular filtration rate (eGFR) of <60 mL/min/1.73 m2 or on chronic dialysis or with a kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 47 publications
2
25
1
Order By: Relevance
“…However, a qualitative study aiming to explore barriers to effective communication amongst CKD patients found that a number of patients described their role to be listening (Lederer et al . ). These patients displayed greater levels of dissatisfaction with their physician relationship and less CKD knowledge in comparison to patients adopting a more active role (Lederer et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, a qualitative study aiming to explore barriers to effective communication amongst CKD patients found that a number of patients described their role to be listening (Lederer et al . ). These patients displayed greater levels of dissatisfaction with their physician relationship and less CKD knowledge in comparison to patients adopting a more active role (Lederer et al .…”
Section: Discussionmentioning
confidence: 97%
“…Lederer also conducted a qualitative study on veterans with chronic kidney disease (CKD) and showed that passive behavior and being just a listener are of the barriers to effective communication between patients and healthcare providers (37). In the same vein, the current study revealed that passive behavior is one of the barriers to dialysis adequacy.…”
Section: Discussionmentioning
confidence: 58%
“…Several studies have examined communication in CKD (Lederer et al, 2015;Walker et al, 2017;Washington, Zimmerman, & Browne, 2016). These studies have found that there are minimal discussions of CKD.…”
Section: 42mentioning
confidence: 99%
“…These studies have found that there are minimal discussions of CKD. For instance, Lederer et al (2015) in a study conducted in the U.S.…”
Section: 42mentioning
confidence: 99%
See 1 more Smart Citation